2019
DOI: 10.1186/s13578-019-0273-3
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ANRIL-mediated inflammation response is involved in protective effect of rhein in uric acid nephropathy rats

Abstract: BackgroundThe aim of this study was to investigate the role of long non-coding RNAs (LncRNAs) antisense non-coding RNA in the INK4 locus (ANRIL) in anti-inflammation of rhein in uric acid nephropathy (UAN) rats.MethodsRat models of UAN were induced by adenine and potassium oxonate. Enzyme-linked immunosorbent assay (ELISA) was performed to assess inflammation factor in serum and supernatant. ANRIL mRNA level was detected using real-time reverse transcription PCR (qRT-PCR). Immunostaining was used to observe pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…These previous findings of lnc‐ANRIL suggest that lnc‐ANRIL might be a mediator of inflammatory and immune responses in various diseases. Thus, we hypothesized that it might be involved in the development of sepsis which is featured by greatly increased immune responses and inflammation, and we observed that lnc‐ANRIL expression in plasma had good predictive value for sepsis risk and was positively correlated with severity and pro‐inflammatory cytokines levels, which was probably derived from that lnc‐ANRIL could promote the progression of inflammation in sepsis through enhancing inflammatory responses or inflammasome expressions through mediating multiple signaling pathways, such as increasing NLRP3 inflammasome by regulating miR‐122‐5p/BRCC3 axis …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…These previous findings of lnc‐ANRIL suggest that lnc‐ANRIL might be a mediator of inflammatory and immune responses in various diseases. Thus, we hypothesized that it might be involved in the development of sepsis which is featured by greatly increased immune responses and inflammation, and we observed that lnc‐ANRIL expression in plasma had good predictive value for sepsis risk and was positively correlated with severity and pro‐inflammatory cytokines levels, which was probably derived from that lnc‐ANRIL could promote the progression of inflammation in sepsis through enhancing inflammatory responses or inflammasome expressions through mediating multiple signaling pathways, such as increasing NLRP3 inflammasome by regulating miR‐122‐5p/BRCC3 axis …”
Section: Discussionmentioning
confidence: 96%
“…Since its first discovery in melanoma, lnc‐ANRIL has been extensively studied, despite the fact that its role in oncology, the association of lnc‐ANRIL with inflammation and immunity has also been found recently . An in vitro and in vivo experiment shows that the inflammatory response mediated by lnc‐ANRIL markedly decreases the protective effect of rhein in rat models of uric acid nephropathy . Another experiment discloses that downregulating lnc‐ANRIL represses the progression of ulcerative colitis, an inflammatory disease, via mediating the miR‐323b‐5p/TLR4/MyD88/NF‐κB signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations